The Next Step Forward in Ubiquitin-Specific Protease 7 Selective Inhibition. Issue 12 (21st December 2017) - Desroses, Matthieu; Altun, Mikael
Abstract : Ubiquitin-specific protease 7 is a validated anticancer target; thus, selective USP7 inhibitors are of great interest. In this issue of Cell Chemical Biology, Lamberto et al. (2017) andPozhidaeva et al. (2017) report important insights into the structural inhibitor-enzyme interplay, lighting the way toward the development of selective inhibitors. Abstract : Ubiquitin-specific protease 7 is a validated anticancer target; thus, selective USP7 inhibitors are of great interest. In this issue of Cell Chemical Biology, Lamberto et al. (2017) and Pozhidaeva et al. (2017) report important insights into the structural inhibitor-enzyme interplay, lighting the way toward the development of selective inhibitors.